Determinan Kejadian Wasting Pada Balita di Provinsi Aceh Tahun 2021 - Wangsa Nata, Mustika Mentari; Setiadi, Yaya (Seminar Nasional Official Statistics, 2023)
Wasting is a form of malnutrition that is dangerous for children. The results of the 2021 Indonesian Nutritional Status Study (SSGI) show that the prevalence of wasting in toddlers in Indonesia is 7.1 percent. This figure has not met the WHO target, namely the prevalence of wasting below 5 percent. In 2021, Aceh Province occupies the third position with the highest prevalence of wasting nationally and is the only province in the Western Region of Indonesia (KBI) that has a prevalence of wasting above 10 percent. If we look at it by district/city, we can see that there are variations in the prevalence of wasting between districts/cities and indicate a regional influence on wasting. The purpose of this research is to find out the general description of the incidence of wasting in children aged 0-59 months (toddlers) in Aceh Province in 2021 and the variables that influence it and its trends. Through a multilevel binary logistic regression model, it was found that gender, birth weight, history of diarrheal disease, and the ratio of health facilities had a significant effect on the incidence of wasting in toddlers in Aceh Province in 2021.